Polycystic Ovary Syndrome: An Updated Overview Foregrounding Impacts of Ethnicities and Geographic Variations - Afrin Yasmin; Shubhadeep Roychoudhury; Arun Paul Choudhury; A. B. Fuzayel Ahmed; Sulagna Dutta; Filomena Mottola; Vivek Verma; Jogen C. Kalita; Dhruv Kumar; Pallav Sengupta; Adriana Kolesarova (Life, 2022)
Polycystic ovary syndrome (PCOS) is one of the most common heterogeneous conditions of the endocrine reproductive system in women of childbearing age. Hyperandrogenism and oligomenorrhea are the two core characteristics of PCOS, a complicated and multifaceted illness. The condition is also linked to several major side effects, which include type 2 diabetes, early atherosclerosis, infertility, and endometrial cancer. There are few facts and statistics available on PCOS prevalence internationally due to the significant degree of geographic and ethnic variance and inconsistency caused by different diagnosis standards. Limited (n = 179) explorations have been made in the context of the prevalence of this complicated illness so far, and out of these, only 55 studies have discussed its association with race and/or ethnicity. However, those studies remain restricted due to the small sample size, biased selection, and the lack of comparative studies. Variations in PCOS prevalence frequency also arise due to different diagnostic criteria, as well as racial and ethnic differences, associated lifestyle factors, and subsequent illnesses that affect the accuracy of the diagnosis. The main objective behind this systematic review is to provide comprehensive epidemiological data on PCOS that is organized geographically. This evidence-based study also provides an overview of the clinical management of PCOS to instigate further research on this complex endocrinological condition and the subsequent development of preventive treatment strategies.